Analysis Of Utilization Of Information Technology In Learning Mathematics - Ulfiyanti Ulfiyanti; Victor R. Sulangi; Sanjte M. Salajang (Universitas Katolik Widya Karya Malang, 2023)
This research aims to determine the utilization of information technology in mathematics learning in Class VIII of SMP Negeri 1 Parigi Selatan. This is a case study that describes an actual situation. In collecting data, the researcher used data collection procedures through interviews with informants, who, in this case, were students, as the source of data and information. Qualitative data analysis in this research uses the SWOT analysis method, which systematically identifies various factors to formulate company strategies. This analysis is based on the logic that can maximize strengths and opportunities while minimizing weaknesses and threats. Then, identify the types of errors and conclude. From the strengths perspective, the results indicate that implementing online learning allows learning resources to be easily accessed online. From the perspective of weaknesses, an unstable internet connection affects students' focus on learning and teaching. From the perspective of opportunities, online learning enhances students' self-learning skills and provides new insights into technology and learning. Finally, from the perspective of threats, students' learning motivation decreases.